Quantitative analysis of venous outflow with photo-plethysmography in patients with suspected thoracic outlet syndrome - Hersant, Jeanne; Ramondou, Pierre; Josse, Charlotte; Lecoq, Simon; Henni, Samir; Abraham, Pierre (Frontiers in Cardiovascular Medicine, 2022)
Background Venous compression is the second most frequent form of thoracic outlet syndrome (TOS). Although venous photo-plethysmography (PPG) has been largely used to estimate the consequences of chronic thromboses (Paget Schroetter syndrome), systematic direct quantitative recording of hemodynamic consequences of positional venous outflow impairment in patients with suspected TOS has never been reported. Objective We hypothesized that moving the arms forward (prayer: “Pra” position) while keeping the hands elevated after a surrender/candlestick position (Ca) would allow quantification of 100% upper limb venous emptying (PPGmax) and quantitative evaluation of the emptying observed at the end of the preceding abduction period (End-Ca-PPG), expressed in %PPGmax. Materials and methods We measured V-PPG in 424 patients referred for suspected TOS (age 40.9 years old, 68.3% females) and retrieved the results of ultrasound investigation at the venous level. We used receiver operating characteristics curves (ROC) to determine the optimal V-PPG values to be used to predict the presence of a venous compression on ultrasound imaging. Results are reported as a median (25/75 centiles). Statistical significance was based on a two-tailed p < 0.05. Results An End-Ca-PPG value of 87% PPGmax at the end of the “Ca” period is the optimal point to detect an ultrasound-confirmed positional venous compression (area under ROC: 0.589 ± 0.024; p < 0.001). This threshold results in 60.9% sensitivity, 47.6% specificity, 27.3% positive predictive value, 79.0% negative predictive value, and 50.8% overall accuracy. Conclusion V-PPG is not aimed at detecting the presence of a venous compression due to collateral veins potentially normalizing outflow despite subclavicular vein compression during abduction, but we believe that it could be used to strengthen the responsibility of venous compression in upper limb symptoms in TOS-suspected patients, with the possibility of non-invasive, bilateral, recordable measurements of forearm volume that become quantitative with the Ca-Pra maneuver. Clinical trial registration [ClinicalTrials.gov], identifier [NCT04376177].